37. Use of a dedicated brain phantom in PET/MR. (December 2017) - Maisonobe, J.-A.; Soret, M.; Khalifé, M.; Jenny, C.; Kas, A.
Abstract : Introduction: The attenuation correction of PET/MR brain imaging is based on a human atlas. However, this atlas cannot be used for phantoms employed for the usual PET/CT experiments. The method based on the DIXON MRI is used instead to separate water and fat tissues and assign them attenuation coefficients at 511 keV. Nevertheless, the usual PET/CT phantoms generate artefacts on the MR-based attenuation maps. Additionally, their materials have different attenuation coefficients from those of human body. Here, we suggest to substitute the MR derived attenuation correction map with a CT derived attenuation correction map for a brain phantom in PET/MR. Methods: Two PET acquisitions of a 3D Hoffman phantom were achieved: one a PET/CT Biograph mCT Flow (Siemens) and one on a Signa PET/MR (GE). Based on these acquisitions, 4 images were reconstructed: 1 with the PET/CT (PETref ) and 3 with the PET/MR (one without attenuation correction (PETNAC ), one corrected using MR-based attenuation map (PETMRAC ) and one corrected using the CT obtained with the PET/CT, registered on the MRI images (PETCTAC ). To evaluate the effect of the different attenuation correction of the PET images, activity concentrations ratio between white matter (WM) and gray matter (GM), as well as between anterior and posterior regions (A/P) and between right and left (R/L) regions, were measured on PETNAC, PETMRAC and PETCTAC and compared to the ratios obtained with PETref . Results: The MR based attenuation correction map of the Hoffman phantom showed artefacts due to segmentation and tissue classification errors. Moreover, for all the reconstructed images, no R/L asymmetry was observed (ratios between 0.96 and 0.99). However, a strong A/P asymmetry with a mean value of 20% was measured in the PETNAC for both WM and GM, versus 1% for the 3 attenuation-corrected images. The WM/GM ratio was underestimated on the PETMRAC (1.84) compared to the CT-based attenuation-corrected ones (1.95 and 1.96 for PETCTAC and PETref, respectively). Conclusions: All the attenuation correction methods allowed to correct the A/P asymmetry, which was increased by the presence of MR coil in the PET/MR system. However, MR-based attenuation-correction map suffered from artefacts and was not adapted to correct the PET image of the Hoffman phantom in PET/MR. The CT-based attenuation correction method used to correct the Hoffman phantom PET/MR image showed ratios comparable to the ones measured on a PET/CT considered as reference.